2019
DOI: 10.1109/access.2019.2935380
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Performance Characterization Considering Six-Degree-of-Freedom Vibration Stress and Aging Stress for Electric Vehicle Battery Under Driving Conditions

Abstract: The battery degradation tests under various stress are critical to understand the relationship between the battery lifespan and the external factors. This paper establishes a battery test bench, which can provide not only the 6-six degree of freedom (DOF) vibration stress but also the charge-discharge stress. By conducting lithium-ion batteries under 6-DOF vibration stress and other reference experiments, the electrochemical impedance spectroscopy (EIS), internal resistances, thermal measurement, open circuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…For the cells experiencing only vibration and the cells experiencing vibration and current pulses, the IR of each of the cells increases slightly over their lifetime as expected with no discernible difference in behavior between the different vibrational loads. The increase in resistance for the cells experiencing only vibration increased by 9%-26%, which is similar to other previous research that has shown internal resistance increases of 5%-25% in cells that experience vibration [34,35]. These results agree with previous research that shows when the dynamic load profile is within the scope described in the UN 38.3 standard, no dynamic vibration-related influence can be observed on the ohmic resistance of the LIBs [5].…”
Section: Internal Resistance and Eissupporting
confidence: 91%
“…For the cells experiencing only vibration and the cells experiencing vibration and current pulses, the IR of each of the cells increases slightly over their lifetime as expected with no discernible difference in behavior between the different vibrational loads. The increase in resistance for the cells experiencing only vibration increased by 9%-26%, which is similar to other previous research that has shown internal resistance increases of 5%-25% in cells that experience vibration [34,35]. These results agree with previous research that shows when the dynamic load profile is within the scope described in the UN 38.3 standard, no dynamic vibration-related influence can be observed on the ohmic resistance of the LIBs [5].…”
Section: Internal Resistance and Eissupporting
confidence: 91%
“…Vibrational energy harvesting is a process by which heat, light, vibration, and other external sources release small amounts of energy that would otherwise be lost to the immediate surroundings. [6] Figure 3 shows different sources of vibrations in electric vehicle. In the event of battery failure, the replacement costs can be reinvested to provide continuous power to batteries or supercapacitors.…”
Section: Figure 3 Vibration Source Identification Methodsmentioning
confidence: 99%
“…A suitable analysis of the sensor under stressed conditions is required to ensure that the considered MEMS-based IMUs will work properly after the installation on a real operating context [18], [19]. However, most of the works found in the literature are based on a static test performed under nominal conditions.…”
Section: Introductionmentioning
confidence: 99%